The Effectiveness of Music Therapy on Stress in Children with Cerebral Palsy: Integrated Literature Review - Permaida Permaida; Allenidekania Allenidekania (Universitas STRADA Indonesia, 2021)
Cerebral palsy is generally caused by ischemia or hemorrhage of the brain blood vessels from the antenatal to the postnatal period. Multidimensional problems in children make him quickly experience negative stress. This study aims to determine the effectiveness of music therapy on stress in children with cerebral palsy. Research using the integrated literature review method took journals from 2012 to 2020 and only eight journals were the inclusion criteria. The results of a journal review show that music therapy given for 10 to 50 minutes to children with cerebral palsy can reduce anxiety, comfort, reduce depression, overcome sleep problems, increase curiosity, focus, not easily forget when studying, and dare to interact with other people. It can be concluded that music therapy is an inexpensive and easy way to deal with stress in children with cerebral palsy so that it can be the right choice when the child is undergoing treatment.